If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(b + -2) = b + 10 Reorder the terms: 5(-2 + b) = b + 10 (-2 * 5 + b * 5) = b + 10 (-10 + 5b) = b + 10 Reorder the terms: -10 + 5b = 10 + b Solving -10 + 5b = 10 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -10 + 5b + -1b = 10 + b + -1b Combine like terms: 5b + -1b = 4b -10 + 4b = 10 + b + -1b Combine like terms: b + -1b = 0 -10 + 4b = 10 + 0 -10 + 4b = 10 Add '10' to each side of the equation. -10 + 10 + 4b = 10 + 10 Combine like terms: -10 + 10 = 0 0 + 4b = 10 + 10 4b = 10 + 10 Combine like terms: 10 + 10 = 20 4b = 20 Divide each side by '4'. b = 5 Simplifying b = 5
| -(4p-4)=-29+7p | | 8r-14=22+4r | | -(4p-4)=-2+7p | | 2t-10=-10+5t | | 6(-2r+2)=12-2r | | 3x=98 | | x^2+6x+46=-6x+10 | | -13+2w=-8w+w | | 2.5m=5.30 | | 2247.995-2161.877=86.125 | | [(8m^2+2m-5)-(10m^2-5m+5)]-(m^2+m+4)= | | (y-5)/3=6 | | 7(-3x+2)=8(3y-2) | | 2x+19=3x-1 | | X-4=.5x+6 | | 7x-23=2x+47 | | (c+3)+2c=21 | | 2x^2+4x-10=4x+8 | | 17-2(x-4)=9 | | y=0.09x+2.89 | | 6d-96=10d | | -31-4=-5-5(1+5x) | | 2(3+4x)-1=21 | | 88=n+n+2(n+20) | | X^2-2x^2+x=0 | | 28=-2(m+4)+m | | 4x-6=x+12 | | 16t^2=9 | | x-10x+21=0 | | 2r+1=15r^2 | | x^2-12=-3+x | | x-16x^2=0 |